CONSTRAINTS TO SWEET ORANGE (Citrus sinensis) MARKETING IN UYO METROPOLIS AKWA IBOM STATE, NIGERIA - Obinaju, L. C.; Jackson, E. E. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the constraints to sweet orange marketing in Uyo metropolis in Akwa Ibom State. The data used for this study was mainly primary data collected through a well-structured questionnaire and analyzed using descriptive statistics, Cost and Returns analysis, means and ranking. A Two – stage sampling technique was used to select these marketers. The first stage involved the selection of three major markets in Uyo metropolis (Udua Itam, Akpan Andem and Udua Afagha) where most of the fruit marketers trade daily. The second stage involved a random selection of thirty (30) sweet orange marketers in Akpan Andem market, twenty-five (25) each from Udua Itam and and Udua Afagha markets respectively, giving a sample size of 80 marketers. The study reveals that sweet orange marketing is a significant economic activity in the area, revealing a total cost of ₦3,775,100, while the total revenue is ₦4,680,400. This results in a net income of ₦905,300, representing a profit margin of 19.34%. Additionally, the return on investment (ROI) is 24.00%, indicating that for every ₦1 invested, the venture generates ₦1.24 in return indicating that the market is profitable. The market is dominated by female marketers (78.75%), aged 21-40 (51.20%), most of the marketers are married (55.00%), with senior secondary school education (51.20%), and household size of 1-5 (77.50%). Retailers (71.25%) dominate the market, with most marketers having 5-8 years of experience (43.80%). However, the market is constrained by price fluctuation (mean = 1.83), seasonality (1.38), and competition among marketers (1.31). The study's findings provide insights into the socio-economic characteristics of sweet orange marketers, marketing channels, cost and returns, and constraints, which can inform policy decisions, marketing strategies, and interventions to enhance the sweet orange industry in Uyo Metropolis.